Final Report SIM.EM-S5 Voltage, Current and Resistance Comparison June 2007-October 2009 - Sanchez, Harold; Cioffi, Jorge; Ventura, Rodrigo; Ferreira, Vitor; Ramos, Rodrigo; Martinez, Alexander; Montaluisa, Julio; Gonzalez, Julio; Postigo, Henry; Hamilton, Francis; Elmquist, Rand; Zhang, Nien Fan; et al. (IOP Publishing, 2014)
This is a report of the results of the second Interamerican Metrology System (SIM) comparison on calibration of digital multimeters, performed for strengthening the interaction among National Metrology Institutes (NMIs) and for establishing the degree of equivalence between those laboratories in accordance with the CIPM Mutual Recognition Agreement. From June 2007 to October 2009, four multimeters were used as traveling standards for measurements in eleven countries, with NIST-USA acting as pilot laboratory. Results for nine measurement points are presented as errors relative to a comparison reference value together with their uncertainty.